2008
DOI: 10.1021/es8017094
|View full text |Cite
|
Sign up to set email alerts
|

Microheterogeneous Concentrations of Singlet Oxygen in Natural Organic Matter Isolate Solutions

Abstract: The binding affinity of a hydrophobic singlet oxygen probe toward natural organic matter isolates was investigated. A linear phase-partitioning model was used to calculate partition coefficients and intramicellar concentrations of singlet oxygen several orders of magnitude larger than those reported by traditional singlet oxygen probes. From the obtained data, a kinetic model was developed to describe the microscopic environment experienced by hydrophobic compounds in natural water systems. Micellar radii and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 42 publications
8
114
2
Order By: Relevance
“…The properties of dissolved species can be reasonably derived by considering the 0.10 µm fraction, which had P a = 1.04⋅10 (Latch and McNeill, 2006;Grandbois et al, 2008). Hydrophobic sites should also be common in suspended particles (Appiani and McNeill, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The properties of dissolved species can be reasonably derived by considering the 0.10 µm fraction, which had P a = 1.04⋅10 (Latch and McNeill, 2006;Grandbois et al, 2008). Hydrophobic sites should also be common in suspended particles (Appiani and McNeill, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have shown that the interaction with DOM enhanced the photodegradation of mirex, 65,66 organic probe compounds of singlet oxygen, 61,67 histidine, 68 and also mercury(0). 69 Compared to free molecules, it has proven difficult to experimentally demonstrate enhanced photoreactions for organic matter-bound microorganisms.…”
mentioning
confidence: 99%
“…Therefore, 1 O 2 could play an important and still poorly recognised role in the photochemical transformation of hydrophobic pollutants, which would be preferentially located in CDOM hydrophobic cores rather than in solution [56,57]. Interestingly, no evidence has been found of a higher photochemical reactivity of CDOM particles compared to dissolved CDOM species, as far as 1 O 2 photoproduction is concerned [58,59].…”
Section: Reaction With 1 Omentioning
confidence: 99%